(untitled) (SCIENCE TIME JOURNAL, 2024)
Thematic, communicative language teaching is an instructional approach that integrates language learning with meaningful themes or topics. This article explores the theoretical foundations of thematic, communicative language teaching, highlighting its key principles and frameworks. The approach is grounded in Communicative Language Teaching (CLT), Task-Based Language Teaching (TBLT), and Content-Based Instruction (CBI), which emphasize the importance of communication, meaningful tasks, and integration of language and content. Constructivism and sociocultural theory also influence this approach, promoting learner-centeredness, authenticity, and social interaction. Thematic, communicative language teaching emphasizes authentic contexts, integrated skills, learner-centeredness, and cultural awareness, aiming to facilitate effective language learning and the development of communicative competence.